Myocardial Infarction with Nonobstructive Coronary Arteries (МINОСА) - a Trendy Term or a New Diagnostic Concept? - S. S. Yakushin (Столичная издательская компания, 2018)
The new term «MINOCA» (myocardial infarction with nonobstructive coronary arteries) emerged in the literature about 5 years ago and characterizes the syndrome with heterogeneous etiology and pathogenesis, which reflects the development of myocardial infarction with non-obstructive lesions of the coronary  arteries, occurring in both cardiological and noncardiac diseases. The article gives detail focus on origin, definition, pathological bases of MINOCA. It also examines the role of coronary (non-obstructive atherosclerosis, microvascular dysfunction, coronary  spasm, "myocardial bridge", coronary  arteries dissection) and  non-coronary reasons, caused  by cardiac (cardiomyopathy, myocarditis) and non-cardiac (pulmonary embolism, thrombophilia) diseases.In analyses of publications much attention is given to the discussion of diagnosis and differential diagnosis, prognosis and treatment of MINOCA. Recommended methods of examination are given depending on the  alleged cause  of the  occurrence of MINOCA. Two clinical cases  demonstrated difficulty in diagnosis of this condition and  the  importance of an individual approach. Attention is also given to the  absence of currently clinical guidelines for the  management of patients with MINOCA and  to the  significant differences in the  use  of different classes of cardiotropic drugs according to different author's mind.Author  gives the  opinion that  MINOCA has  a certain practical significance as a preliminary "diagnosis" before  final establishing the  disease. In conclusion, it is emphasized that the MINOCA syndrome terminology and characteristic is controversial now. This mind confirmed by a new definition of this condition in the Forth Universal Definition of Myocardial Infarction (European Society of Cardiology, 2018).